2021
DOI: 10.1017/s0007114521003226
|View full text |Cite
|
Sign up to set email alerts
|

Meal frequency and incidence of type 2 diabetes: a prospective study

Abstract: Dietary habits play an important role in the development of obesity and type 2 diabetes. However, evidence on association between diet frequency and type 2 diabetes was limited and inconclusive. We aimed to examine the association between meal frequency and risk of type 2 diabetes. The cohort study used data from China Health and Retirement Longitudinal Study of 8874 community-dwelling people aged over 45 years. Participants were classified as eating 2 meals/d, 3 meals/d and 4 meals/d. Multiple Poisson regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…A follow-up study of American health professional men showed that lower eating frequency was associated with a higher risk of T2DM [ 8 ]. Besides, another study conducted on Chinese community residents showed that eating four meals a day was related to a lower risk of T2DM compared to eating three meals a day, while eating two meals a day showed no relationship with T2DM [ 7 ]. In addition, there was a randomized trial focusing on prediabetes patients, suggesting that increasing the frequency of eating under isocaloric conditions can provide a variety of metabolic benefits, including improved glucose metabolism [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A follow-up study of American health professional men showed that lower eating frequency was associated with a higher risk of T2DM [ 8 ]. Besides, another study conducted on Chinese community residents showed that eating four meals a day was related to a lower risk of T2DM compared to eating three meals a day, while eating two meals a day showed no relationship with T2DM [ 7 ]. In addition, there was a randomized trial focusing on prediabetes patients, suggesting that increasing the frequency of eating under isocaloric conditions can provide a variety of metabolic benefits, including improved glucose metabolism [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, research on this topic has produced inconclusive results. A prospective study conducted on Chinese community residents showed that increasing diet frequency may reduce the risk of T2DM [ 7 ]. Another study of American health professional subjects indicated that lower eating frequency was associated with a higher risk of T2DM [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several dietary habits, such as meal frequency, seem to have potential effects on human health and metabolism, especially on diet-related diseases [ 11 , 12 ]. Previous studies indicated that increased meal frequency is associated with a lower risk of obesity [ 13 ] and improved lipid profiles [ 14 , 15 ]. In regard to lipid metabolism, a previous meta-analysis of randomized controlled trials (RCTs) suggested that higher meal frequency improves lipid profile [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Mekary et al ( 10 ) showed both high- and low-frequency eating patterns were linked to T2D in 46 289 US women as part of the Nurses’ Health Study. Wang et al ( 11 ) showed eating 4 meals/d, compared to three meals was associated with lower risk of developing T2D (RR 0⋅76; 95 % CI 0⋅60, 0⋅97) in a Chinese population of 8874 adults over 45. In addition to meal frequency, unhealthy dietary habits such as high salt and fried food intakes have been shown to impact risk of hypertension, overweight and obesity ( 12 , 13 ) alongside T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Increased sodium intake was shown to significantly ( P < 0⋅05) decrease healthy lifestyle scores across the four quartiles. Further research is needed to evaluate the combined associations between meal frequency ( 11 ) , high salt intakes ( 16 ) , frequency of fried/grilled-food consumption ( 13 ) with the prevalence of T2D.…”
Section: Introductionmentioning
confidence: 99%